T Cell Subsets in the Germinal Center: Lessons from the Macaque Model - Vaccari, Monica; Franchini, Genoveffa (Frontiers in Immunology, 2018)
Germinal centers (GCs) are organized lymphoid tissue microstructures where B cells proliferate and differentiate into memory B cells and plasma cells. A few distinctive subsets of highly specialized T cells gain access to the GCs by expressing the B cell zone–homing C-X-C chemokine receptor type 5 (CXCR5) while losing the T cell zone–homing chemokine receptor CCR7. Help from T cells is critical to induce B cell proliferation and somatic hyper mutation, and to limit GC reactions. Follicular CD4+ T helper cells (TFH) are required for the formation of GCs and for the generation of long-lived, high-affinity B cells. Regulatory CD4+ and CD8+ T (TFR) cells co-localize with TFH cells and keep their expansion in check, thus limiting GC reactions. A cytotoxic CXCR5pos CD8+ T cell subset has been described in GCs in humans: although low in number, GC– CD8+ T cells can expand rapidly during certain viral infections. Because these subsets find their home in secondary lymphoid tissues (lymph nodes and spleen) that are difficult to obtain in humans, GC–homing T cells have been extensively studied in mice. Nevertheless, significant limitations in using this model, such as evolutionary divergences between mice and humans and the lack of an optimal mouse model for certain human diseases, have prompted investigators to characterize GC–homing T cells in macaques instead. This review will focus on discoveries made in macaques, particularly in the non-human primate models of SIV and SHIV infection. Indeed, experimental studies in these models have allowed researchers to gain insight into the relative role of follicular T cell subsets in HIV progression, virus persistence, and specific B cell responses induced by HIV vaccines. These discoveries have prompted the testing of novel approaches aimed to manipulate follicular T cells to increase the efficacy of HIV vaccines and to eliminate HIV reservoirs.